Fine‐Tuning of the Carbon Dioxide Capture Capability of Diamine‐Grafted Metal–Organic Framework Adsorbents Through Amine Functionalization. Issue 3 (22nd December 2016) - Jo, Hyuna; Lee, Woo Ram; Kim, Nam Woo; Jung, Hyun; Lim, Kwang Soo; Kim, Jeong Eun; Kang, Dong Won; Lee, Hanyeong; Hiremath, Vishwanath; Seo, Jeong Gil; Jin, Hailian; Moon, Dohyun; et al.
Abstract: A combined sonication and microwave irradiation procedure provides the most effective functionalization of ethylenediamine (en) and branched primary diamines of 1‐methylethylenediamine (men) and 1, 1‐dimethylethylenediamine (den) onto the open metal sites of Mg2 (dobpdc) (1 ). The CO2 capacities of the advanced adsorbents1‐en and1‐men under simulated flue gas conditions are 19 wt % and 17.4 wt %, respectively, which are the highest values reported among amine‐functionalized metal‐organic frameworks (MOFs) to date. Moreover, 1‐den exhibits both a significant working capacity (12.2 wt %) and superb CO2 uptake (11 wt %) at 3 % CO2 . Additionally, this framework showcases the superior recyclability; ultrahigh stability after exposure to O2, moisture, and SO2 ; and exceptional CO2 adsorption capacity under humid conditions, which are unprecedented among MOFs. We also elucidate that the performance of CO2 adsorption can be controlled by the structure of the diamine ligands grafted such as the number of amine end groups or the presence of side groups, which provides the first systematic and comprehensive demonstration of fine‐tuning of CO2 uptake capability using different amines. Abstract : MOFs capture CO2 : Diamine‐grafted metal–organic framework (MOF) CO2 adsorbents are prepared through amine functionalization. The frameworks show excellent CO2 adsorption and working capacities; superior recyclability; ultrahigh stability after exposure to O2, moisture, and SO2 ; and exceptional CO2 adsorption capacity under humid conditions that are unprecedented among MOFs.